2015
DOI: 10.1038/aps.2014.148
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of cathepsin L sensitizes human glioma cells to ionizing radiation in vitro through NF-κB signaling pathway

Abstract: Aim: Cathepsin L, a lysosomal cysteine proteinase, is exclusively elevated in a variety of malignancies, including gliomas. In this study we investigated the relationship between cathepsin L and NF-κB, two radiation-responsive elements, in regulating the sensitivity of human glioma cells ionizing radiation (IR) in vitro. Methods: Human glioma U251 cells were exposed to IR (10 Gy), and the expression of cathepsin L and NF-κB was measured using Western blotting. The nuclear translocation of NF-κB p65 and p50 was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…Moreover, NF-κB can bind to the human Snail promoter in the region between -194 and -78 bp and increase the transcription of Snail [60] . Our group found that CTSL acts as an upstream regulator of NF-κB activation [61] . Thus, we suspected that the regulation of CTSL by Snail may be achieved via NF-κB or CUX1.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, NF-κB can bind to the human Snail promoter in the region between -194 and -78 bp and increase the transcription of Snail [60] . Our group found that CTSL acts as an upstream regulator of NF-κB activation [61] . Thus, we suspected that the regulation of CTSL by Snail may be achieved via NF-κB or CUX1.…”
Section: Discussionmentioning
confidence: 98%
“…NF-κB can be activated through either RelA:p50-based classical (canonical) or RelB:p52-based alternative (non-canonical) pathway by a multitude of stimulants including IR [ 14 ]. Although most studies have focused on the classical pathway [ 15 17 ], we and others found that RelB is uniquely expressed at the high levels in advanced PCa and the levels of nuclear RelB are particularly associated with the patients Gleason scores [ 18 , 19 ]. Additionally, as a typical NF-κB regulated protein, MnSOD is adaptively stimulated by IR-induced ROS production partially through RelB-mediated transcriptional activation, and selectively preventing RelB nuclear translocation resulted in enhancing radiosensitivity of PCa cells [ 20 ] .…”
Section: Introductionmentioning
confidence: 99%
“…Overexpression of CTSB decreased chemotherapeutic temozolomide drug-induced glioma cell death and promoted the mesenchymal transition [29]; while knockdown of CTSB caused cell cycle arrested in G0/G1 phases and enhanced radiosensitivity [30]. Elevated CTSB may, like cathepsin L, contribute to radio-resistance in human glioma cells by activation of its downstream NF-κB [31]. The expression of NF-κB1 was revealed to be increased with the increasing degree of malignancy in glioma [32].…”
Section: Discussionmentioning
confidence: 96%